2005
DOI: 10.1161/01.cir.0000153351.86708.f7
|View full text |Cite
|
Sign up to set email alerts
|

Different Contributions of Endothelin-A and Endothelin-B Receptors in Postischemic Cardiac Dysfunction and Norepinephrine Overflow in Rat Hearts

Abstract: Background-Endothelin (ET)-1 and norepinephrine (NE) are involved in myocardial ischemia/reperfusion injury. We investigated the role of ET-1 in ischemia/reperfusion-induced NE overflow and cardiac dysfunction using a selective ET A receptor antagonist (ABT-627), a selective ET B receptor antagonist (A-192621), and the spotting lethal (sl) rat, which carries a naturally occurring deletion in the ET B receptor gene. Methods and Results-According to the Langendorff technique, isolated hearts were subjected to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
5
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 46 publications
4
44
5
4
Order By: Relevance
“…These findings were probably unexpected and contradict, in part, those reported 8 previously by the same group under identical experimental conditions; in this study, 8 endogenously generated and exogenously administered ET-1 evoked noradrenaline overflow and produced left ventricular dysfunction. The elegant study by Tawa et al raises several questions that were thoroughly addressed in their experiments.…”
Section: Pathophysiological Role Of Et-1contrasting
confidence: 77%
See 1 more Smart Citation
“…These findings were probably unexpected and contradict, in part, those reported 8 previously by the same group under identical experimental conditions; in this study, 8 endogenously generated and exogenously administered ET-1 evoked noradrenaline overflow and produced left ventricular dysfunction. The elegant study by Tawa et al raises several questions that were thoroughly addressed in their experiments.…”
Section: Pathophysiological Role Of Et-1contrasting
confidence: 77%
“…However, these effects diminished during subsequent phases (2-24 h) of evolving myocardial infarction. The data reported by Tawa et al, in context with previous work, 8,9 shed further light to a long-standing caveat on the role of the ETB receptor. Nevertheless, it should be emphasized that this information applies only to acute myocardial ischaemia and should not be extrapolated to other chronic disease states.…”
Section: Pathophysiological Role Of Et-1supporting
confidence: 66%
“…[7][8][9][10]14 In addition, we obtained evidence that exogenously applied ET-1 to the ischemic heart further enhanced the NE overflow and exacerbates the postischemic cardiac dusfunction. 10 In the present study, we expected that exogenously applied big ET-1 would cause deterioration of cardiac function following the global ischemia and reperfusion, because exogenously applied big ET-1 exerts qualitatively similar effects to ET-1, in the cardiovascular system in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, both selective ET A receptor antagonists and non-selective ET A /ET B receptor antagonists exhibited protective effects against the postischemic cardiac dysfunction. [7][8][9][10] Enhancement of cardiac sympathetic nerve activity and its consequent effect on norepinephrine (NE) overflow from the nerve endings has also been considered as a factor that aggravates cell damage in ischemic myocardium. 11 In fact, it has been demonstrated that the negative modulation of NE release significantly suppresses postischemic cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation